A revision of Callulops doriae (Anura: Microhylidae), with descriptions of four new species - Kraus, Fred (Zootaxa, 2019)
I investigate the taxonomy of frogs currently assigned to the single species Callulops doriae, which is unique in the genus for its warty, dark-spotted dorsum and large yellow or orange blotches in the groin and on the hidden surfaces of the thighs. I show that many species are currently encompassed under this single name, I remove Manthophryne neuhaussi from synonymy, and I describe four new species, three of which have long been in museum collections, and one of which is newly collected by me. Each of these new species is most readily distinguished by their unique color patterns, but additional morphological features―primarily morphometric―also serve to distinguish among them. Despite this partition of C. doriae, additional museum specimens cannot be assigned to any of the species treated here and certainly represent unrecognized species. But the poor states of preservation of some of these and the absence of color-pattern information in life preclude describing them until new material of each is available. Three of the six species treated herein, which occur in the southern portion of the Papuan Peninsula, were previously included in a molecular phylogeny, and inferred dates of divergence for them accord well with the geological dynamism of this region created by opening of the Woodlark Rift. In two cases, pairs of species are reported in general sympatry, and elevational data suggest that these species are likely to segregate elevationally where their ranges approach each other. At least four of the species treated herein are known to produce viscous glandular secretions that presumably deter predators, and I describe the defensive display of one of these, which I presume is aposematic.